2014
DOI: 10.1016/j.bbi.2013.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Toxoplasma gondii cyst distribution in the forebrain associate with individual variation in predator odor avoidance and anxiety-related behavior in male Long–Evans rats

Abstract: Toxoplasma gondii (T. gondii) is one of the world’s most successful brain parasites. T. gondii engages in parasite manipulation of host behavior and infection has been epidemiologically linked to numerous psychiatric disorders. Mechanisms by which T. gondii alters host behavior are not well understood, but neuroanatomical cyst presence and the localized host immune response to cysts are potential candidates. The aim of these studies was to test the hypothesis that T. gondii manipulation of specific host behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 52 publications
5
63
0
1
Order By: Relevance
“…Consistent with the findings of previous studies in mice, T. gondii had no obvious preference for specific brain regions (12)(13)(14). In addition, no other study has reported clear evidence to support the idea that parasite localization plays a critical role in the behavioral changes induced by T. gondii infection (9,15,16,43). Here, our histopathological analysis showed that meningitis in the cortex was more severe than that in other regions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with the findings of previous studies in mice, T. gondii had no obvious preference for specific brain regions (12)(13)(14). In addition, no other study has reported clear evidence to support the idea that parasite localization plays a critical role in the behavioral changes induced by T. gondii infection (9,15,16,43). Here, our histopathological analysis showed that meningitis in the cortex was more severe than that in other regions.…”
Section: Discussionsupporting
confidence: 81%
“…First, the relationship between parasite localization in the brain and behavioral changes has been investigated, with a previous study reporting that T. gondii has no obvious tropism in the brain (12)(13)(14)(15). However, another study found that tissue cyst density in amygdalar areas (the medial and basolateral amygdala) is 2-fold higher than that in nonamygdalar areas (9), whereas the presence of tissue cysts in the forebrain contributes to the attenuation of predator odor aversion and anxiety-like behavior (16). Overall, these studies suggest that the T. gondii cyst distribution contributes to behavioral changes, but this still requires further investigation.…”
mentioning
confidence: 99%
“…In contrast, many studies have demonstrated that adult rats are one of the most resistant hosts to T. gondii infection with respect to clinical toxoplasmosis and this phenomenon has been known for more than half a century (Benedetto et al, 1996;Evans et al, 2014;Fujii et al, 1983;Lewis and Markell, 1958;Li et al, 2012;Nakayama and Hoshiai, 1960). The similarity between the clinical course in rat and human toxoplasmosis suggests the use of rats as an ideal model to elucidate the mechanism of Toxoplasma infection in humans (Darcy and Zenner, 1993;Santoro et al, 1987;Zenner et al, 1998Zenner et al, , 1999aZenner et al, , 1999b.…”
Section: Introductionmentioning
confidence: 82%
“…Mechanisms of such anatomically restricted changes remain presently unknown. It has earlier been suggested that T. gondii preferentially concentrates in certain brain regions, and this tropism can explain behavioural changes post-infection through local manipulation of neuronal signalling and/or damage [2,46,47]. Two early studies in this regard reported a rather widespread occurrence of tissues cysts in a variety of brain regions [2,47].…”
Section: Discussionmentioning
confidence: 99%